The Adventitia Layer Modulates the Arterial Wall Elastic Response to Intra‐Aortic Counterpulsation: In Vivo Studies. Issue 12 (4th July 2013) - Cabrera‐Fischer, Edmundo I.; Bia, Daniel; Zócalo, Yanina; Wray, Sandra; Armentano, Ricardo
Abstract There is a relationship between the intra‐aortic balloon pumping (IABP) benefits and the dynamic behavior of muscular arteries, which is associated with induced changes on the vessel walls through an endothelial‐dependent mechanism. The arterial wall elastic behavior is influenced by adventitial function; however, no studies were performed in order to elucidate if this layer plays a role in the changes determined by IABP. Our aim was to quantify acute IABP effects on the mechanical properties of muscular arteries in induced acute heart failure (AHF), before and after adventitia removal. Pressure and diameter were recorded in the iliac arteries (IA) of sheep (n = 7), before and during 1:2 IABP: (i) in control state (CS) with intact IA, (ii) in CS after IA adventitia removal, and (iii) in de‐adventitialized IA after AHF. Conduit function, compliance and arterial distensibility were calculated in each state. During CS, IABP resulted in intact IA dilatation and in an increase in conduit function, compliance and distensibility; adventitial removal determined an increase of arterial stiffness with respect to the CS, which decreased when IABP was used; the increase in arterial stiffness observed after adventitia removal was also detected in AHF state; IABP improves conduit function and arterial stiffness in de‐adventitialized arteries, both before and during AHF. However, the improvement in these properties was lower than in intact arteries. Before and after AHF induction, the improvements of conduit function and arterial distensibility determined by IABP in intact IA were significantly reduced after adventitia removal. Adventitial layer integrity would be necessary to maximize IABP‐related beneficial effects on arterial system properties.